DAMPAK SOSIAL EMOSIONAL REMAJA SELAMA SOCIAL DISTANCING : LITERATURE REVIEW - Ghifari Andini Mukti; Hadi Pratomo; Nur Khotimah Elfiyani; Rizky Dhahifa Wahyuni; Safitri Widayanti Putri (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
To control the COVID-19 Pandemic, the Indonesian Government has issued a large scale social restriction policies. The community including adolescent are expected to remain at home and required to attend school from home. This study aims to assess the impact of large scale social restriction to the social-emotionalcondition of the adolescents.This study is a literature review using online journal search engine PubMed, Wiley, ScienceDirect, SpingerLink, Proquest, BioMed Central Health and google schoolar. The criteria of the journal published in 2020. The results showed that there were changes in adolescents' interactions with peers and parents. Meanwhile, the emotional condition showed that girls are more prone to experiencing emotional problems than boys. The emotional problems that appear are stress, depression, and anxiety.